Perspectives of Power-Oriented Economic Growth Conversion (with Special Reference to Russia) - Kuznetsova, Natalia P. (Ekonomika, 2006)
The slogan of economic growth acceleration and GDP doubling in Russia is very popular and appears almost in every public speech and economic program of political parties. However. few Russian (and not only Russian) economists, sociologists and philosophers reveal the reasons for a fast or slow economic growth, its structure, sources, factors and the algorithm of conversion from the energyoriented to innovation-oriented type. Economic and political discussions take into account neither the volatility, craftiness and even pseudo-evidence of statistics, nor the illusion of sustainable development. the impossibility of the economic and ecological industrial systems’ harmony based on the exaggerated ideas about the unlimited intellectual and power possibilities of man. There exists a non-equivalent power exchange between the socio-economic system and Nature, and hence the evolutionary (ecological and economic) crisis is inevitable. The ways of overcoming this misbalance point out either to reduction of nature exploitation or non-traditional sources of power use. But the implementation of these methods is impossible for the most part of the world, particularly for those countries which possess large amounts of natural and power resources. The latter could lead to the so-called “economic diseases” (Holland, Venezuela, etc.). Keeping in mind these considerations, the purpose of the present paper is to analyze modern economic growth indicators connected with the energy factor. to introduce new types of economic growth - innovation-oriented and energyoriented - and to propose the possible convergence of these types in different scenarios of Russian industrial development.